MAHSULOT SIFATI NAZORATIDA STATISTIK USULLARNING QO‘LLANILISHI (GISTOGRAMMA MISOLIDA) - Maxmonov, U.A. (SCIENCE and SOCIETY, 2024)
This article discusses the theoretical and practical issues of applying statistical control methods to improve quality control in the production process. An algorithm for statistical control has been developed. Based on the obtained measurement results, a histogram and its construction are shown, which is one of the methods of statistical control.
Keywords: product; quality; quality control; statistical control; histogram